A studyof the relationbetween net revenue and social-environmental investments in three financial institutions - Coelho, Guilherme; Lorandi, Jôisse Antônio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The Social Balance Sheet is a statement which allows us to identify the impacts caused by the company regarding the social and environmental aspects. This research intends to investigate the investments on the social context – internal and external – as much as the environmental context, that have been done by three large brazilian banks in the last four years (2009 to 2012), and then compare it with the growth rate of the profits obtained during the same period. The analysis is conducted from values took from the following Social Balance Sheet indicators: calculation base, internal social indicators, external social indicators, environmental indicators. The analyzed financial institutions – Banco do Brasil, Caixa Econômica Federal, Bradesco – are extremely relevant on the national financial system’s context. Other large-sized banks haven’t been published the Social Balance Sheet in the latest years, while the ones that are being analyzed on this research keep publishing the statement annually. As a part of the theoretical framework of the study, it has been focused on topics like: characteristics of the Social Balance Sheet, social responsibility and sustainability among financial institutions, and the main aspects of correlated legislation. The results indicate a significant difference between net income and social-environmental investments in the analyzed companies.